THE EFFECT OF THE APPLICATION OF THE UPRIGHT POSITION ON DURATION TIME DELIVERY - Apri Sulistianingsih; Yeti Septiasari (Gaster, 2022)
Background:Childbirth is a natural process in a woman's life cycle. The care given should also return to the body's physiology. The upright position is considered a position that helps the fetus decline faster, but so far there are still mothers who lie down during childbirth. Research objective:This study aims to determine the effect of the application of the upright position on the time of delivery in women giving birth in PMB, Pringsewu Regency. Method: This study uses a quasi-experimental design with a non-equivalent group pre-post test. The research subjects were mothers who gave birth normally in PMB Pringsewu Regency. The sample of this research is. The inclusion criteria in this study were normal mothers who were willing to be respondents in PMB Pringsewu Regency. Research analysis using Independent T test. Results ; showed that the first stage of time in the control group was 7.53 ± 0.84 hours, while the first stage of time in the intervention group was 4.85 ± 0.62. The second stage of time in the control group was 50.38 ± 6.24 minutes, while the second stage of the intervention group was shorter at 32.53 ± 5.30 minutes. The results of the statistical test showed that there was a significant difference so that there was an effect of applying the upright position to the length of time in the active phase of the first stage of labor and the second stage of labor in women giving birth at PMB Pringsewu (p value = 0.000). The application of an upright position in maternity makes the duration of labor faster than the lying position